2020
DOI: 10.1038/s41598-020-65603-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pulmonary tuberculosis in Chinese adults with type 2 diabetes: a retrospective cohort study in Shanghai

Abstract: To estimate the incidence of pulmonary tuberculosis (PTB) in Chinese diabetes patients and to evaluate the effect of blood glucose on PTB risk, a retrospective cohort study was built based on the diabetes management system in Shanghai and included 240,692 adults aged 35 or above. Incidences of PTB in all diabetes patients and by subgroups were calculated and compared. Multivariable Cox regression models with restricted cubic splines were used to evaluate the association of fasting plasma glucose (FPG) with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
3
3
1
Order By: Relevance
“…The analyses for both TB prevalence and TB incidence in several subgroups showed significant differences. Male DM patients with lower BMI had higher TB prevalence and incidence rates; these findings were like those identified in the general population and could be found in retrospective cohort study conducted in Shanghai ( 6 ). A history of previous TB was identified as a high-risk factor for developing TB by many studies ( 9 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The analyses for both TB prevalence and TB incidence in several subgroups showed significant differences. Male DM patients with lower BMI had higher TB prevalence and incidence rates; these findings were like those identified in the general population and could be found in retrospective cohort study conducted in Shanghai ( 6 ). A history of previous TB was identified as a high-risk factor for developing TB by many studies ( 9 ).…”
Section: Discussionsupporting
confidence: 79%
“…The study also observed a higher prevalence of bacteriologically-confirmed TB in known DM patients than that for the general population based on data obtained from the Fifth National Tuberculosis Prevalence Survey. Compared with a retrospective cohort study conducted in Shanghai ( 6 ), our study obtained a much higher TB incidence rate in larger areas. Our active TB incidence was also higher than that obtained in a cohort study conducted in the Republic of Korea ( 7 ) and lower than that obtained in Indonesia ( 8 ).…”
Section: Discussioncontrasting
confidence: 66%
“…This study found for the first time that the significant increases of these three genes may be related to the inflammatory reaction after MTB infection, and also play important roles in the pathogenesis of various types of diabetes 96,97 . The current research showed that the risk of pulmonary TB in T2DM patients was about two to three times that of the general population, 98 and the results of this study suggest that TB may also increase the incidence rate of diabetes. Amy2a5 is an amylase alpha 2 that catalyzes the hydrolysis of starch into sugar, providing energy for the body 44 .…”
Section: Discussionsupporting
confidence: 56%
“…Inclusion criteria: Patients diagnosed with TB and DM. Inclusion criteria of TB dependedon the Chinese guidelines for the diagnosis and treatment of TB (2020 version) [11]: (1) The sputum smear was positive for acid-fast bacilli; (2) Mycobacterium tuberculosis cogroup was cultured in sputum, bronchoalveolar lavage fluid or pleural effusion; (3) The nucleic acid of Mtb and/or Mtb culture was positive in sputum, bronchoalveolar lavage fluid, or pleural effusion; (4) the pathological staining of lung tissue specimens was positive for acid-fast bacilli, or the nucleic acid of Mtb was positive in lung tissue specimens from the lesion site. The diagnosis of pulmonary TB could be clarified if any of the above four items were met.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The growing prevalence of diabetes mellitus (DM) has emerged as one of the major global health challenges and may lead to an increase in the burden of TB. China has a heavy burden of TB with DM (patients had both tuberculosis and diabetes) [ 1 ]. Studies have shown that due to the impaired immune function of DM patients, the risk of active TB increases by 3 times [ 2 ].…”
Section: Introductionmentioning
confidence: 99%